The Role of Human Resource Development (HRD) in Improving Employee Competence and Competitiveness - Mendrofa, Niken Yoladin; Kurniawan, Ly Dany; Erlyana, Erlyana; Pelle, Imanuel; Mulyandi, M Rachman (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This study explores how Human Resource Development (HRD) contributes to strengthening employee competence and competitiveness in organizations facing global and technological changes. Using a descriptive qualitative method, the research reviews various theories and previous findings on HRD. The results reveal that HRD enhances both technical and soft skills through systematic training, career development initiatives, performance reviews, and supportive work conditions. HRD also elevates employee competitiveness by fostering motivation, adaptability, and innovation. Overall, HRD is shown to be a key driver in developing high-quality human capital and sustaining organizational competitive strength.